The Effect of Bay Leaf Extract Gel on Increasing Fibroblasts in Traumatic Ulcers Healing Process - Firawan, Kurnia Nisa Putri; Kusuma, Ira Anggar; Istiadi, Hermawan; Santoso, Oedijani (Universitas Diponegoro, 2025)
The wound healing process of traumatic injuries in the oral cavity involves four stage: hemostasis, inflammation, proliferation, and remodeling. Fibroblast cells are essential for the wound healing process, appearing on the 3rd day and reaching their peak on the 7th day after injury. This study reveals that bay leaf extract can accelerate wound healing process by mitigating inflammation and enhancing fibroblast cell activity. This research utilized a post-test only control group design. Fifteen male Wistar rats divided in 3 groups equally: control group and 2 groups were given 5% and 10% of the bay leaf extract gel was applied twice a day until the 5th day. The results indicated that the group treated with 10% bay leaf extract gel had significantly higher value compared to the control group and the group treated with 5% bay leaf extract gel. In this study, we can learn that bay leaf extract gel can increase of fibroblast cells in the ulcer healing process.